The pollution of polychlorinated biphenyls (PCBs) waste from PLN electrical activities - Romianingsih, Ni Putu Wulan (Asian Journal of Toxicology, Environmental, and Occupational Health, 2023)
PCB waste pollution from PLN (State Electricity Company) electrical activities is a serious problem that affects the environment and public health. This article discusses the sources and impacts of PCB waste pollution, as well as the steps that can be taken to address it. PCB waste originates from transformers, capacitors, and other electrical equipment used by PLN, and it can contaminate the soil, water, air, and surrounding living organisms. The consequences include ecosystem damage, disturbance of ecological balance, health risks, and even economic implications. To tackle this issue, effective waste management technologies such as retrofilling, thermal processes, and sodium processes need to be implemented. Additionally, strict waste management policies and regulations should be established, and public awareness of the dangers of PCB waste should be raised. By adopting these measures, we can mitigate the negative impacts of PCB waste pollution and work towards a cleaner and healthier environment.